Investigating the influence of processing parameters on bimetallic catalysts for high-yield carbon nanotube synthesis - A. Okesola, Abayomi; Mensah-Darkwa, K.; B. Maledi, Nthabiseng; Andrews, Anthony (Asia-Pacific Journal of Science and Technology, 2024)
The efficient synthesis of carbon nanotubes (CNTs) remains a challenge, and optimizing processing conditions for high-quality CNT production is a subject of ongoing research. In this study, the influence of processing parameters on the structure-property relationships of synthesized Fe-Ni bimetallic catalysts and the yield of carbon nanotubes (CNTs) was investigated. The study also aimed to optimize the synthesis conditions for the Fe-Ni bimetallic catalyst supported on CaCO3 and examine the effect of CNT purification on the final product. The CNTs were synthesized using a chemical vapor deposition process with an Fe-Ni bimetallic catalyst supported on CaCO3, and the effects of processing parameters such as pre-calcination temperature, stirring speed, support mass, and pre-calcination time on the yield and properties of the CNTs were analyzed. The synthesized CNTs were then characterized using SEM, FT-IR, BET, XRD, and Raman spectrometers to assess their structure and properties. The study revealed that optimizing the synthesis conditions led to increased graphitization and crystallinity of the CNTs. A maximum CNT yield of 376% was obtained under the optimal conditions of a reaction temperature of 700°C, a time of reaction of 90 min, and nitrogen and C2H2 flow rates of 294 mL/min and 193 mL/min, respectively. CNT purification was found to be effective in reducing impurities and functionalizing the CNTs for easy dispersion. The findings provide valuable insights for the development of efficient methods for the large-scale production of high-quality CNTs.